2016
DOI: 10.4103/0253-7613.193308
|View full text |Cite
|
Sign up to set email alerts
|

Introducing structured viva voce examination in medical undergraduate pharmacology: A pilot study

Abstract: Objective:Viva voce examination is an important tool of evaluation in medical examinations marred by high subjectivity. Gross subjectivity in viva voce assessment can be reduced by structuring it.Materials and Methods:The marks obtained in theory and viva voce (traditional viva voce examination [TVVE]) of I sessional, II MBBS students were compared and a huge disparity was identified. A structured viva voce examination (SVVE) was then proposed and experimented as an objective and standardized alternative. Sets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…The uniqueness of the practical treatment planning approach could be the main reason the students were engaged in learning. The use of oral assessments or ''viva voces'' to assess students' readiness for practice is still common practice in other disciplines [19][20][21]. In radiation therapy, the verbalization of how the students would have optimized their treatment plans, providing a rationale for their approaches, is likely to reveal gaps in knowledge and identify students' strengths and weaknesses.…”
Section: Discussionmentioning
confidence: 99%
“…The uniqueness of the practical treatment planning approach could be the main reason the students were engaged in learning. The use of oral assessments or ''viva voces'' to assess students' readiness for practice is still common practice in other disciplines [19][20][21]. In radiation therapy, the verbalization of how the students would have optimized their treatment plans, providing a rationale for their approaches, is likely to reveal gaps in knowledge and identify students' strengths and weaknesses.…”
Section: Discussionmentioning
confidence: 99%
“…Student's feedback was quite encouraging with 83% overall acceptability and almost 66% preferred SVVE. 12 Hence, a great deal of work is to be done to bring about effective implementation of viva voce examinations.…”
Section: Discussionmentioning
confidence: 99%
“…The feasibility of structured viva-voce examination (SVVE) in undergraduate course to reduce the subjectivity of marking was assessed (Dhasmana et al, 2016). The authors observed that student's perception of SVVE was encouraging and satisfying, as compared to traditional viva-voce exams.…”
Section: Assessmentmentioning
confidence: 99%